Estrategias logísticas para la mejora del proceso de distribución de mercancías de los principales supermercados de cadena ubicados en los barrios Villa Country y Prado de la ciudad de Barranquilla (2018)
This degree work analyzes in a way in which the urban logistics distribution is performed in the major chain supermarkets located in the towns of the districts "El Prado" and "Villacountry" belonging to the city of Barranquilla, scenarios where it is committed to the efficiency of the supply chain for the type of products and which is based on the activity of loading and unloading of trucks. Support, considers the research and tabulation of data, which is a utility for the last stage of the supply chain.